ANALISIS FAKTOR PERBEDAAN HASIL BELAJAR KELAS XI IPS PELAJARAN EKONOMI SMA ASISI PONTIANAK - Ulansari, Titin; Ulfah, Maria; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is an analysis on the academic achievement different on eleventh grade student of SMA Santo Fransiskus Asisi between morning and afternoon class on Economy subject. The goals of this research are to describe and analyze factors which affect the achievement.Â  The method used in this research is qualitative descriptive in form of comparative casual study, and the sources of data are primer and seconder. The Techniques used in this research are interview using guidelines on a teacher whom teach the subject, observation using guidelines, documentation. Based on the data analysis, the average score are: class A score is 19, 05 with 47, 63 points, class B is 19,44 on score and 48,61 points. The results are categorized low due to the academic achievement which are below 50% from 100%. The factors that affect the academic achievement are poor quality building, incomplete facilities, and student numbers in morning class. Afternoon class achievement are categorized as intermediate. The score of class C is 28,05 with 70,13 points. The score of class D is 27,05 with 68,08. Academic achievement on afternoon class are categorized as intermediate with the average points 70,13 from interval point 1-100,wich are above 50%.Keywords: Analysis, affective factor, academic achievement